2010
DOI: 10.1021/la100858q
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Organic Monolayers onto Hydrogen-Terminated Silicon: 1-Alkynes Are Better Than 1-Alkenes

Abstract: Recently, a new method for the preparation of high-quality organic monolayers with 1-alkynes at room temperature in the dark (i.e., without any external activation) was reported. To pinpoint the precise origin of this self-assembly process and to compare the reactivity of 1-alkenes and 1-alkynes toward hydrogen-terminated Si(111) [H-Si(111)], we followed the gradual formation of both monolayers at room temperature by static water contact angle measurements. Subsequently, attenuated total reflection infrared sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 49 publications
7
80
2
Order By: Relevance
“…We note that similar data with carbonyl-related peaks were observed for the attachment of 1-alkynes to alumina surfaces, 29 whereas this contrasts strongly with the formation of the signals obtained for Si−CHCH-bound monolayers obtained from 1-alkynes on H-terminated Si(111) surfaces. 3,61 Stimulated by earlier work in our group on the oxidative binding of C16YNE on porous anodic alumina, 29 we also used 2-hydroxyhexadecanoic acid (2HHDA) as a reference. Ter Maat et al observed a remarkable resemblance between the XPS and IR spectra obtained from C16YNE-modified and 2HHDA-modified porous anodic alumina surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We note that similar data with carbonyl-related peaks were observed for the attachment of 1-alkynes to alumina surfaces, 29 whereas this contrasts strongly with the formation of the signals obtained for Si−CHCH-bound monolayers obtained from 1-alkynes on H-terminated Si(111) surfaces. 3,61 Stimulated by earlier work in our group on the oxidative binding of C16YNE on porous anodic alumina, 29 we also used 2-hydroxyhexadecanoic acid (2HHDA) as a reference. Ter Maat et al observed a remarkable resemblance between the XPS and IR spectra obtained from C16YNE-modified and 2HHDA-modified porous anodic alumina surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4 Moreover, hydrosilylation reactions of molecular silanes typically require ultraviolet illumination, whereas H-Si(111) surfaces react with unsaturated hydrocarbons under visible-light illumination 51 as well as under certain circumstances in the dark at room temperature. 50,78 The mechanisms for the reactions of Grignard reagents, alkenes, and alkynes at H-Si(111) surfaces involve electron transfer kinetics that closely parallel the reaction of CH 3 OH with HSi(111) surfaces. These reactions are known to be sensitive to the bulk electronic structure of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 34 which nucleophiles, including alcohols, alkenes, alkynes, and Grignards, can undergo reaction with H-Si(111) surfaces in the presence or absence of an oxidant and/or an illumination source.…”
Section: Ivf Relevance To Othermentioning
confidence: 99%
“…181 The increased reactivity of alkynes allows the hydrosilylation reaction to occur under very mild conditions (room temperature) in the dark, 182 while producing higher-quality surfaces than obtained with alkenes. 183 Concerns that elevated temperatures may activate functional groups and enable side reactions with the Si−H surface have limited the widespread use of thermally activated hydrosilylation. However, it has been found that this method allows for the fabrication of high-quality SAMs, which can be transformed into reactive functional groups such as carboxylic acids.…”
Section: Hydrosilylation Of H-terminated Surfacesmentioning
confidence: 99%